2007
DOI: 10.1177/009164710703500302
|View full text |Cite
|
Sign up to set email alerts
|

Learning Agility in Clergy: Understanding the Personal Strategies and Situational Factors that Enable Pastors to Learn from Experience

Abstract: Relatively little is known about the ongoing development of pastors as leaders. This study focused on learning agility, the combination of personal strategies and situational factors that pastors rely on to capture the lessons their experiences teach them. Interviews with 100 senior pastors indicated that the situational factors associated with learning for pastors were those that pushed them to step to the edge of their comfort zones, requiring them to draw on God and others, manage significant change, manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Finally, similar to Eichinger, Lombardo, and colleagues, McKenna, Boyd, and Yost (2007) examined learning agility by exploring both the situational and personal factors that influence individuals' learning from experiences. On the basis of 100 interviews with pastors, the authors concluded that one's ability to learn from experience—which they refer to as learning agility—is enhanced by situational factors such as access to role models, exposure to novel experiences that involve change and complexity, and opportunities for reflection.…”
Section: Learning Agility: a Literature Review And Constructive Critiquementioning
confidence: 99%
“…Finally, similar to Eichinger, Lombardo, and colleagues, McKenna, Boyd, and Yost (2007) examined learning agility by exploring both the situational and personal factors that influence individuals' learning from experiences. On the basis of 100 interviews with pastors, the authors concluded that one's ability to learn from experience—which they refer to as learning agility—is enhanced by situational factors such as access to role models, exposure to novel experiences that involve change and complexity, and opportunities for reflection.…”
Section: Learning Agility: a Literature Review And Constructive Critiquementioning
confidence: 99%
“…Prior literature helps explain why this characteristic is shared among the study participants. For example, in a study by McKenna, Boyd, and Yost (2007), 100 lead pastors were interviewed to identify the strategies they use to navigate difficult situations successfully. The senior pastors who showed successful coping strategies referred to their own attributes, which included their lifelong desire to learn, curiosity, and sense of wonder.…”
Section: Discussionmentioning
confidence: 99%
“…These pastors also discussed their propensity to learn by observation and consult with role models. Pastors often referenced that they tried to emulate others, a cognitive strategy in which pastors learned from or patterned themselves after a role model (McKenna et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Those pastors who learn from mistakes will possess the emotional agility and dexterity needed to survive the difficult demands of the ministry (McKenna, Boyd, & Yost, 2007). In addition, a pastor who wishes to be successful in his or her professional role must be adaptable to different professional circumstances.…”
Section: Self-management In the Pastoratementioning
confidence: 99%